DEEP-AI Pedagogical Model for Strengthening Al-Qur'an Interpretation Literacy in Islamic Religious Education - Supriyadi, Tedi; Julia, J; Supriadi, Udin; Rahminawati, Nan; Sarvinoz Baxtiyorovna, Allayorova (Jurnal Pendidikan Agama Islam, 2025)
Purpose - This study aims to develop and evaluate the effectiveness of the DEEP-AI (Developing Exegetical Engagement and Proficiency with AI Assistance) Model with four learning stages, namely Decode, Explore, Examine, Project–Artificial Intelligence Assisted as a technology-based interpretation learning approach that is gradual, integrative, and adaptive. Design/Method/Approach - This study used a developmental research approach conducted in three stages: (1) needs analysis through questionnaires and interviews with 105 students, (2) model design and validation by three experts (interpretation, Islamic pedagogy, and learning technology), and (3) limited testing on 35 students. The model was evaluated quantitatively through pre-test and post-test analysis using normality tests, paired t-tests, and N-Gain calculations, and qualitatively through student perceptions. Findings - The results showed a significant improvement (p < 0.001) in all aspects of interpretive literacy, with N-Gain values between 0.64 and 0.73, as well as excellent student perception scores (average of 4.64 on a scale of 5). Research Implication /Limitation - The DEEP-AI model has proven to be effective and has been very well received by students in improving their interpretation literacy. Originality/Value - This study offers an AI-based interpretation learning model that is pedagogically designed, competency-oriented, and relevant to the needs of Islamic education in the digital age